Congenital Infiltrating Lipomatosis of the Face: A Case Report - Asha Mahadevappa; Vanisri H. Raghavan; Sunila Ravishankar; Gubbanna V. Manjunath (Case Reports in Pediatrics)
Congenital infiltrating lipomatosis of the face is a rare lesion that comprises a subgroup of lipomatous tumor-like lesions of infancy and childhood. It is characterized by (1) no encapsulation, (2) diffuse infiltration of mature adipose tissue over normal muscle fiber and surrounding structures of face, (3) osseous hyperplasia of subjacent bone, and (4) a high recurrence rate. We report a case of a nine-month-old infant who presented with swelling over right face since birth. Early diagnosis of this lesion provides better surgical approach to control the infiltrative nature of its growth with recurrence and aesthetic appearance.